Pseudo-zwitterionic metal organic framework composite material as well as preparation method and application thereof
By preparing the pseudo-zwitterionic metal-organic framework composite UNBP, the problems of performance interference and insufficient selectivity of existing materials in high-salt environments have been solved, achieving efficient glycopeptide enrichment and simple preparation, which is suitable for glycoproteomics analysis and disease biomarker discovery.
Patent Information
- Application Number
- CN202511273174.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-08
- Publication Date
- 2025-12-12
AI Technical Summary
Existing zwitterionic hydrophilic interaction chromatographic materials suffer from performance interference and insufficient selectivity in high-salt environments. Their preparation processes are complex, resulting in low glycopeptide enrichment efficiency, which fails to meet the needs of glycoproteomics analysis.
A pseudo-zombie metal-organic framework (UNBP) composite material was prepared by a one-step solvothermal method. The pseudo-zombie structure was constructed by combining metal-organic framework, amino and boric acid groups, and a polymer rich in amide groups was introduced to improve hydrophilicity and dispersibility.
It enables efficient and selective capture of glycopeptides in complex biological samples, simplifies the preparation process, is suitable for large-scale production, and provides an efficient glycoproteomics analysis tool.
Smart Images

Figure CN121103338A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional nanomaterials and their biomedical applications, specifically to a method for preparing a metal-organic framework composite material (UNBP) for biological sample pretreatment and target molecule enrichment, and its application in glycoproteomics analysis and biomarker analysis. Background Technology
[0002] Protein glycosylation is one of the core regulatory mechanisms of life activities, playing a crucial role in cell signaling, immune regulation, and disease development. Its abnormalities are closely related to the occurrence and development of major diseases such as cancer. Therefore, accurate capture and analysis of glycopeptides are essential for discovering disease mechanisms, identifying biomarkers, developing drugs, and early diagnosis. However, due to the extremely low abundance of glycopeptides in biological samples, efficient and specific enrichment is a key bottleneck in current glycoproteomics research. Hydrophilic interaction chromatography (HILIC) has become an important technique for glycopeptide enrichment due to its ease of operation and compatibility with mass spectrometry. However, current zwitterionic HILIC materials face two major challenges in practical applications: firstly, their performance is affected by high-salt environments and their selectivity is insufficient, resulting in low capture efficiency for key low-abundance glycopeptides such as sialylated peptides; secondly, their preparation process is complex and demanding, with uneven polymerization of the stationary phase, which not only induces non-specific adsorption but also severely restricts the reproducibility and large-scale production of the materials, making it difficult to meet the stringent requirements of applications. Therefore, in order to break through the existing technical bottlenecks and promote the in-depth development of glycosylation analysis in the field of precision medicine, it is urgent to develop a new generation of zwitterionic HILIC enrichment material with a well-defined structure, good performance and simple preparation, so as to improve the recovery rate of glycopeptides and expand their application scope. This invention is proposed to solve the above problems and has important technical innovation value and broad application prospects. Summary of the Invention
[0003] To address the shortcomings of existing technologies, such as low selectivity, insufficient hydrophilicity, and complex preparation processes, this invention aims to provide a novel pseudo-zwitterion metal-organic framework composite material (UNBP), its preparation method, and its applications. This technical solution, through innovative material design, aims to significantly improve the enrichment efficiency and analytical reliability of low-abundance glycopeptides, exhibiting high efficiency and stability, especially when processing complex biological samples.
[0004] To achieve the above objectives, the present invention adopts the following technical solution:
[0005] In a first aspect, the present invention provides a pseudo-zwitterionic metal-organic framework composite material.
[0006] The composite material is characterized in that it comprises: (a) a metal-organic framework: composed of metal ions or metal clusters coordinated with at least two organic ligands, wherein the first organic ligand provides an amino group and the second organic ligand provides a borate group, which together construct a pseudo-zwitterionic structure on the surface of the framework; and (b) a polymer: a polymer rich in amide groups, which is attached to or encapsulated in the metal-organic framework.
[0007] The preferred embodiment of the technical solution of the present invention is as follows:
[0008] The metal-organic framework has a topology selected from UiO-66, MIL-53 (Al), MIL-101 (Cr), MOF-5 or MIL-88A (Fe), wherein the most preferred is the UiO-66 topology with zirconium as the metal center.
[0009] The first organic ligand providing the amino group is 2-aminoterephthalic acid.
[0010] The second organic ligand providing the boric acid group is selected from one of 4-carboxyphenylboronic acid, 5-boronic acid-1,3-benzenedicarboxylic acid, or (2,5-dicarboxyphenyl)boronic acid, with 4-carboxyphenylboronic acid being the most preferred.
[0011] The polymer rich in amide groups is selected from polyvinylpyrrolidone or polyamide, with polyvinylpyrrolidone being the most preferred.
[0012] The metal-organic framework material significantly improves hydrophilicity through the pseudo-zwitterionic structure composed of amino and borate groups, utilizing the electrostatic interaction of zwitterions; while the polymer rich in amide groups introduces amide functional groups with more affinity sites into the metal framework material, thereby improving the overall dispersibility of the material.
[0013] Secondly, the present invention provides a method for preparing the above-mentioned composite material.
[0014] This method is a one-step solvothermal method, characterized by the following steps: (1) Preparation of reaction solution: In an organic solvent (such as N,N-dimethylformamide), a metal salt (such as zirconium chloride), a first organic ligand providing an amino group (such as 2-aminoterephthalic acid), a second organic ligand providing a boric acid group (such as 4-carboxyphenylboronic acid), and a polymer rich in amide groups (such as polyvinylpyrrolidone) are mixed. (2) Adjustment and mixing: An acidic regulator (such as acetic acid and concentrated hydrochloric acid) is added to the above mixture and ultrasonically mixed thoroughly. (3) Solvothermal synthesis: The mixed solution from step (2) is transferred to a reaction vessel and a solvothermal reaction is carried out at a specific temperature and time. (4) Post-treatment: After the reaction is completed, the product is centrifuged, washed, and dried to obtain the pseudo-zwitterionic metal-organic framework composite material UNBP.
[0015] As a preferred embodiment of the preparation method of the present invention:
[0016] The preferred molar ratio of the metal salt, the first organic ligand, and the second organic ligand is 1:1.
[0017] The amount of acetic acid used is 3 mL, and the amount of concentrated hydrochloric acid used is 75 μL.
[0018] The preferred temperature for the solvothermal reaction is 120℃-150℃, and the preferred time is 12h-24h. Preferably, the temperature for the solvothermal reaction is 150℃, and the preferred time is 12h.
[0019] Thirdly, the present invention provides the application of the above-mentioned composite material in the enrichment of glycopeptides or glycoproteins.
[0020] Specifically, a method for enriching glycopeptides or glycoproteins is provided, which includes incubating the composite material with a biological sample containing glycopeptides or glycoproteins to allow the target molecules to bind to the composite material, followed by enrichment through solid-liquid separation.
[0021] As a preferred embodiment of the present invention:
[0022] The biological samples were immunoglobulin G, bovine serum albumin, and mouse liver tissue.
[0023] The beneficial effects of this invention are as follows:
[0024] Compared with the prior art, the present invention has the following significant advantages:
[0025] (1) Structural Innovation and Synergistic Performance Enhancement: This invention innovatively integrates three functional groups—amino, boric acid, and amide—into a single system. The pseudo-zwitterionic surface formed by the amino and boric acid groups provides strong hydrophilic forces, while the amide groups introduced by the polymer not only further enhance hydrophilicity but also provide additional hydrogen bonding sites, improving the dispersibility and stability of the nanomaterials in the aqueous phase, achieving a synergistic effect of "1+1+1>3". Due to its unique structural design, the composite material of this invention exhibits superior hydrophilicity and excellent anti-interference ability, enabling it to efficiently and selectively capture glycopeptides even in complex biological samples.
[0026] (2) The preparation process is simple and easy to scale up: This invention adopts a one-step solvothermal method, adding all components to the reaction system at once, which greatly simplifies the preparation process and shortens the production cycle. The reaction conditions are mild, the repeatability is good, and the cost is controllable, making it fully capable of large-scale industrial production and laying the foundation for the widespread application of this material.
[0027] (3) Wide range of applications: The high-performance enrichment material provided by this invention effectively solves the key bottleneck in glycoproteomics analysis, and provides an efficient and reliable new tool for the discovery of biomarkers for major diseases such as cancer and the development of early clinical diagnostic drugs. It has important social value and broad market prospects. Attached Figure Description
[0028] Figure 1 The scanning electron microscope image of UNBP, a metal-organic framework material with a pseudo-zwitterionic structure, in Example 1 of this invention;
[0029] Figure 2 The infrared spectrum of UNBP, a metal-organic framework material with a pseudo-zwitterionic structure, in Example 1 of this invention;
[0030] Figure 3 This is the X-ray diffraction pattern of UNBP, a metal-organic framework material with a pseudo-zwitterionic structure in Example 1 of the present invention.
[0031] Figure 4 This is a schematic diagram of the mass spectrometry signal of glycopeptides in human immunoglobulin G enzymatic hydrolysis products after enrichment by the pseudo-zwitterionic metal-organic framework material UNBP.
[0032] Figure 5 This is a schematic diagram of the mass spectrometry signals of glycopeptides in the enzymatic hydrolysis products of human immunoglobulin G at different concentrations after enrichment by the pseudo-zwitterionic metal-organic framework material UNBP.
[0033] Figure 6This is a schematic diagram of the glycopeptide mass spectrometry signals in the enzymatic hydrolysis products of human immunoglobulin G and bovine serum albumin at different mass ratios after enrichment by the metal-organic framework material UNBP with a pseudo-zwitterion structure.
[0034] Figure 7 This is a statistical chart showing the number of glycopeptides identified in the enzymatic hydrolysis products of mouse liver samples after enrichment with UNBP, a metal-organic framework material with a pseudo-zwitterionic structure. Detailed Implementation
[0035] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention based on the content of this description. The present invention can also be implemented or applied through other specific embodiments, and various modifications and changes can be made according to different applications.
[0036] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below. The terminology used in the embodiments of the present invention is for describing specific embodiments and is not intended to limit the scope of protection of the present invention.
[0037] This invention does not limit the source of raw materials used. Unless otherwise specified, all raw materials used in this invention are common commercially available products in this technical field. This invention provides a method for preparing, characterizing, and applying a pseudo-zombie ionic metal-organic framework material (UNBP), including the following steps:
[0038] Example 1
[0039] Synthesis of UNBP: 0.070 g zirconium chloride (ZrCl4, 3 mmol), 0.027 g 2-aminoterephthalic acid (C8H6O4, 1.5 mmol), 0.025 g 4-carboxyphenylboronic acid (C8H6O4, 1.5 mmol), and polyvinylpyrrolidone (PVP, 0.03 mmol) were dissolved separately in N,N-dimethylformamide (13 mL in total), and the solutions were ultrasonically mixed separately and then combined. 4 mL of glacial acetic acid and 50 μL of concentrated hydrochloric acid were added, and the mixture was ultrasonically mixed for 10 min. The mixed solution was transferred to a reaction vessel and heated at 150 °C for 12 h. The resulting pseudo-zwitterionic metal-organic framework composite material was denoted as UNBP.
[0040] Example 2
[0041] (1) The pseudo-zwitterionic metal-organic framework composite material (hereinafter referred to as UNBP material) prepared in Example 1 was characterized by scanning electron microscopy (SEM), and the results are as follows: Figure 1 As shown. By Figure 1It can be seen that the UNBP material exhibits a uniform and regular octahedral morphology with a uniform particle size distribution, indicating that the preparation method of the present invention can obtain a composite material with good morphology.
[0042] (2) To verify the chemical structure of the material, Fourier transform infrared (FT-IR) spectroscopy analysis was performed on the UNBP material prepared in Example 1, as well as the raw materials UiO-66-NH2, polyvinylpyrrolidone (PVP), and 4-carboxyphenylboronic acid. The spectra are shown below. Figure 2 As shown. Analysis Figure 2 It can be seen that the UNBP material spectrum retains UiO-66-NH2 at 770 cm⁻¹. -1 The characteristic Zr-O vibrational peaks at 1654 cm⁻¹ confirm that the material contains a basic framework structure of UiO-66. Compared to UiO-66-NH₂, the UNBP material's spectrum shows a more pronounced Zr-O vibrational peak at 1654 cm⁻¹. -1 A characteristic stretching vibration peak corresponding to the carbonyl group (C=O) in PVP appeared at 1297 cm⁻¹. Meanwhile, the spectrum of the UNBP material showed a peak at 1297 cm⁻¹. -1 A characteristic stretching vibration peak corresponding to the BO bond of the borate group in 4-carboxyphenylboronic acid appeared at the specified location. The appearance of the above characteristic peak objectively confirms that PVP and 4-carboxyphenylboronic acid have been successfully composited into the framework of UiO-66-NH2, indicating that the pseudo-zwitterionic composite material described in this invention has been successfully prepared.
[0043] (3) X-ray diffraction (XRD) analysis was performed on the UNBP material prepared in Example 1 and UiO-66-NH2 as a precursor. The spectra are shown below. Figure 3 As shown in the figure. The results show that, compared with the diffraction pattern of UiO-66-NH2, the positions of the main diffraction peaks of the UNBP material did not change significantly, and the peak positions and shapes maintained good consistency. This indicates that, in the composite process described in this invention, the crystal structure and topological configuration of the material were well preserved and not destroyed.
[0044] Example 3
[0045] To verify the enrichment performance of the UNBP material of this invention, an enrichment experiment was conducted on the trypsin hydrolysate of human immunoglobulin G (IgG) in this embodiment. Specifically, the UNBP material prepared in Example 1 was dispersed in a 95% acetonitrile / 1% trifluoroacetic acid aqueous solution and incubated with the IgG hydrolysate at 37°C for 30 minutes. After incubation, the precipitate was collected by centrifugation and washed twice with the above solution to remove impurities, followed by elution with a 30% acetonitrile / 0.1% trifluoroacetic acid aqueous solution. The collected eluent was analyzed by MALDI-TOF-MS, and the results are as follows. Figure 4As shown in the mass spectrum, up to 40 IgG glycopeptide signals with significant signal-to-noise ratios were successfully identified after enrichment, while non-glycopeptide signals were effectively suppressed. This result strongly demonstrates that the material of this invention can achieve efficient and highly selective enrichment of glycopeptides in standard protein samples.
[0046] Examples 4-6
[0047] To evaluate the enrichment sensitivity of the UNBP material of this invention, the human immunoglobulin G enzymatic hydrolysate from Example 3 was diluted to three different concentrations: 10 fmol / μL. -1 1 fmol / μL -1 0.1 fmol / μL -1 All other enrichment and analytical conditions remained consistent with those in Example 3. The mass spectrometry analysis results are as follows: Figure 5 As shown, the results indicate that even at sample concentrations as low as 0.1 fmol / μL... -1 Even at the same time, the material of this invention was still able to successfully identify six characteristic glycopeptides with significant signal-to-noise ratios. These experimental results demonstrate that the enrichment method provided by this invention has excellent sensitivity and can meet the analytical needs of low-abundance samples.
[0048] Examples 7-9
[0049] To evaluate the enrichment selectivity of the UNBP material of this invention in complex samples, the enzymatic digest of human immunoglobulin G was mixed with bovine serum albumin (BSA), a high-abundance non-glycoprotein, at mass ratios of 1:100, 1:500, and 1:1000 to simulate different levels of background interference. Other enrichment and analysis conditions were the same as in Example 3. Mass spectrometry analysis results are as follows: Figure 6 As shown, the results indicate that even under harsh conditions with background interference up to 1000 times (mass ratio 1:1000), the material of this invention can still successfully identify 15 characteristic glycopeptides with significant intensity. This result confirms that the material of this invention has extremely high enrichment selectivity, can effectively resist interference from a large number of non-glycopeptides, and is suitable for the analysis of complex biological samples.
[0050] Example 10
[0051] This embodiment aims to verify the enrichment performance of UNBP material for glycopeptides in real, complex biological samples (mouse liver tissue) to evaluate its feasibility in practical applications. First, trypsin digestion products from mouse liver tissue were used as the enrichment target. The specific enrichment process, including buffer formulation, incubation conditions, washing, and elution steps, was consistent with Example 3. Subsequently, the collected eluent was desalted and analyzed in depth using liquid chromatography-mass spectrometry (LC-MS / MS). This experiment was conducted on five independent mouse liver samples, and representative analytical results are shown below. Figure 7As shown in the figure, analysis revealed that the material of this invention successfully enriched and identified 907, 1107, 839, 1106, and 873 complete N-glycopeptides in five independent liver samples, respectively, with an average of 966 complete N-glycopeptides identified and a coefficient of variation as low as 12.05%. This result strongly demonstrates that the UNBP composite material prepared by this invention is not only suitable for standards but can also be successfully applied to real biological samples with extremely complex compositions, efficiently and reliably enriching a large number of endogenous glycopeptides, indicating its high practical value in glycoproteomics research and preclinical studies.
[0052] In summary, this invention successfully designed and prepared a novel pseudo-zwitterionic metal-organic framework composite material. Systematic experimental verification confirmed that this material exhibits superior comprehensive performance due to its unique dynamic charge-complementary surface and synergistic effects of multiple functional groups: firstly, it has high enrichment efficiency, capable of efficiently capturing large amounts of glycopeptides from standards and real biological samples; secondly, it exhibits excellent detection sensitivity, demonstrating strong enrichment ability even at extremely low concentrations at the femtomolar level; and thirdly, it has excellent selectivity, specifically separating target glycopeptides even under non-glycoprotein background interference of up to 1000 times. These characteristics, combined with the one-step mild synthesis process provided by this invention, effectively overcome the performance and practicality bottlenecks of existing technologies. Therefore, this invention not only provides a powerful new analytical material but also offers a reliable, efficient, and potentially large-scale solution for cutting-edge fields such as glycoproteomics, disease biomarker screening, and precision medicine, demonstrating significant technological advancement and broad market application prospects.
[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that any equivalent modifications or adjustments to the embodiments (including but not limited to raw material substitution, process optimization, or the addition of auxiliary components) made without departing from the technical principles of the present invention, as well as any extended applications based on the technical essence of the present invention, all fall within the scope of protection of the present invention. Specifically, the above embodiments are only used to illustrate the preparation method and application of the pseudo-zwitterionic metal-organic framework material UNBP, and are not necessary conditions for implementing the present invention. Any improvements or derivative schemes based on the concept of the present invention fall within the scope of the claims and disclosure of the present invention.
Claims
1. A nanocomposite material, characterized in that, The composite material comprises: (a) a metal-organic framework comprising a metal ion or a metal cluster, and at least two organic ligands coordinated to the metal ion or the metal cluster, wherein the first organic ligand comprises an amino group and the second organic ligand comprises a borate group; and (b) an amide-rich polymer attached to or encapsulated therein on or within the metal-organic framework.
2. The nanocomposite material as described in claim 1, characterized in that, The metal-organic framework has a topology of UiO-66, MIL-53 (Al), MIL-101 (Cr), MOF-5, or MIL-88A (Fe); preferably, the metal-organic framework has a topology of UiO-66, and the metal ion or metal cluster is zirconium.
3. The nanocomposite material as described in claim 1, characterized in that, The first organic ligand containing an amino group is 2-aminoterephthalic acid.
4. The nanocomposite material as described in claim 1, characterized in that, The second organic ligand containing the boric acid group is one or a combination of 4-carboxyphenylboronic acid, 5-boronico-1,3-benzenedicarboxylic acid, or (2,5-dicarboxyphenyl)boronic acid; preferably, the second organic ligand is 4-carboxyphenylboronic acid.
5. The nanocomposite material as described in claim 1, characterized in that, The polymer rich in amide groups is polyvinylpyrrolidone or polyamide.
6. A method for preparing the nanocomposite material according to any one of claims 1-7, characterized in that, The method is a one-step solvothermal method, comprising the following steps: (a) mixing a metal source, a first organic ligand containing an amino group, a second organic ligand containing a boric acid group, and a polymer rich in amide groups in an organic solvent to form a reaction precursor solution; (b) carrying out a solvothermal reaction of the reaction precursor solution in a closed reactor; (c) obtaining the nanocomposite material by separation and purification steps after the reaction is completed.
7. The method as described in claim 8, characterized in that, In step (a), an acid regulator was also added for mixing.
8. The method as described in claim 7, characterized in that, The metal source is zirconium chloride, the first organic ligand is 2-aminoterephthalic acid, the second organic ligand is 4-carboxyphenylboronic acid, the polymer is polyvinylpyrrolidone, the organic solvent is N,N-dimethylformamide, and the acidity regulator includes acetic acid and hydrochloric acid; the temperature of the solvothermal reaction is 120°C to 150°C, and the reaction time is 12 hours to 24 hours.
9. A method for enriching glycopeptides or glycoproteins in a sample, characterized in that, The method includes the following steps: (a) providing a nanocomposite material according to any one of claims 1-5; (b) contacting and incubating the nanocomposite material with a sample containing glycopeptides or glycoproteins to bind the glycopeptides or glycoproteins to the nanocomposite material; and (c) separating the nanocomposite material bound to the glycopeptides or glycoproteins from the sample matrix.
10. The method as described in claim 9, characterized in that, The sample is a biological sample, preferably human serum, animal tissue, or cell lysate.